Amblyomma scalpturatum Neumann, 1906 (Acari: Ixodidae): confirmation in Acre State, Brazil, and description of parasitism in a human - Aguirre,André de Abreu Rangel (2019)
Abstract Amblyomma scalpturatum is a tick species that is unique to South America. It is commonly associated with the Amazon biome and has been reported in some Brazilian states. This tick species exhibits host specificity: it parasitizes tapirs and suidae. Its role in transmitting pathogens to humans is still unknown. Amblyomma scalpturatum is known to be a human-biting tick; however, there is only one report showing that humans make suitable hosts for this species. The knowledge of tick fauna is lacking in the Acre State. This study collected free-living ticks with the aim of finding new records in Acre State. Collections were carried out in Amazon forest fragments in Rio Branco municipality. An A. scalpturatum specimen was identified and submitted sequencing of the ITS-2 gene. This study presents the first molecular confirmation of A. scalpturatum collected in situ in Acre State, North Region, Brazil. This study also presents the first record of a successfully completed feeding by an A. scalpturatum nymph on a human host in the North region of Brazil. Further investigation is needed to ascertain the complete life cycle of this tick species, its seasonality in the environment, and its relationship to pathogens and competence to transmit them.